Distribution Of Monovalent Particles in The Structure Of A Sentence (Journal of Pedagogical Inventions and Practices, 2025)
The study explores the distribution and syntactic behavior of monovalent particles within sentence structures in modern English. It investigates their grammatical functions, their relation to verb valency, and the mechanisms through which they influence clause organization. The analysis considers various syntactic environments where monovalent particles occur, such as declarative, interrogative, and imperative constructions. By examining their distributional patterns, the study identifies their role in shaping the informational structure and communicative function of a sentence. The findings reveal that monovalent particles play a significant part in maintaining syntactic economy, expressing subtle semantic nuances, and influencing sentence modality and emphasis